ARABIC IN CERTIFIED TRASLATORS’ WORK - STYSZYNSKI, Marcin (Comparative Legilinguistics, 2009)
The present paper concerns Arabic in certifi ed translators’ work. The paper contains a selection of examples translated from Arabic into Polish from a large domain of translation studies. I would like to underline that the present examples concern Polish language, with the English version not being a primary focus. Th is paper will deal with two important points (i) suitable words which express exact meanings and terms and (ii) the correctness of administrative style in some Arabic documents. Th e author will also examine the composition of Arabic texts and selection of information during the translation process.